Wear and mechanical characteristics of coated Ti-6Al-4 V alloy with an alumina-13 wt.% titania -40 wt.% yitrium stabilized zirconia ceramic composite via plasma spraying technique - N. Senthilkumar; G. Perumal; K. Palanikumar; B. Deepanraj; M. Shameer Basha (Results in Engineering)
In this study, the wear and mechanical behaviour of three coatings made from micron-sized powders of alumina (Al2O3) (ALO), (ii) Al2O3–40 wt.%8 yitrium stabilized zirconia (YSZ) (A4ZO), and (iii) Al2O3–13 wt.% titanium dioxide (TiO2)-40 wt.%8YSZ (AT4ZO) on the Ti-6Al-4V alloy (TAV) using plasma spraying is examined and compared. In addition to conducting wear tests, measurements of the coatings' porosity, microhardness, adhesive/cohesive strength, scanning electron microscope (SEM), and X-ray diffraction (XRD) were conducted to better comprehend the causes of wear. It has been demonstrated that the composite coating AT4ZO greatly improves the wear resistance over others. In comparison to A4ZO and alumina coatings, the resistance to wear of the AT4ZO composite coating is greater by 1.5 times than that of A4ZO and around 2.5 times higher than that of the latter. Comparing the three pairs of coatings, the cumulative wear loss of the AT4ZO/Alumina pair is substantially less. The effective melting and spreading of the molten droplets in the composite coating results in a dense microstructure and enhanced cohesion between the splats, which contributes to the coating's exceptional wear resistance. The improved wear resistance is attributed to increased splat cohesion strength and the phase transition toughening process caused by the presence of tetragonal phases and lubricating effect of the TiO2, according to an assessment of the wear tracks. When referring to the composite coating, the main wear process is found to be due to micro cracking and micro chipping combined with abrasive wear, whereas the wear process of the alumina coating is found to be abrasive wear with splat dislodgement. The correlation between fracture length and scratch resistance was established through experimental investigation It is evidence that our experimental results significantly corroborate these theoretical implications.